PEMBERDAYAAN MASYARAKAT KAMPUNG ADAT CIPTARASA BERBASIS ON LINE UNTUK MENINGKATKAN DAYA SAING - Mardiah, Mardiah; Aliyyah, Rusi Rusmiati; Suryani, Danu; Gemina, Dwi; Effane, Anne; Apriliasari, Ajeng (LPPM Universitas Islam 45 Bekasi, 2025)
The community empowerment program in Kampung Adat Ciptarasa, Sukabumi Regency, was implemented through an online-based approach as a form of community service to support the development of household industries. The primary problems identified among the partners included weak institutional governance, low product quality and production capacity, limited market access, and inadequate knowledge of business bookkeeping. The program engaged 20 partners who demonstrated willingness and commitment to participate as assisted partners. The implementation methods consisted of training and mentoring conducted both in person and online, alongside simulations and hands-on practice. The training materials covered: (1) strengthening institutional governance and business management; (2) improving product quality and production capacity; (3) developing business and digital marketing strategies; and (4) practicing simple bookkeeping for household industry actors. The results indicated an improvement in partners’ knowledge and skills in managing their businesses, utilizing digital marketing technology, and keeping financial records in a more organized manner. This program motivated household industry actors to seize market opportunities and optimize local potential. In conclusion, online-based empowerment proved effective in fostering the economic independence of the community, while serving as a concrete implementation of the Tri Dharma of Higher Education by Universitas Djuanda, with direct benefits for the assisted partners’ welfare.